EFFECT OF ABDOMINAL COMPRESSION BINDER ON PULMONARY FUNCTION IN ADULT PARAPLEGICS - ARIJIT KUMAR DAS; TUSHAR J. PALEKAR; RASIKA PANSE (International Journal of Pharma and Bio Sciences, 2015)
Respiratory dysfunction is a major source of morbidity and mortality in patients with spinal cord injury (SCI) and an abdominal binder improves efficiency of the diaphragm and in-turn has an effect on respiratory function. To find out the effect on Pulmonary Function with Abdominal Compression Binder in Adult Paraplegics. Method: 20 Paraplegic was selected, informed consent was taken. In sitting position spirometry was performed. FVC, FEV1/FVC and PEFR were recorded without the abdominal binder. The Abdominal binder was applied and a Pressure biofeedback machine was placed between the binder and fastened to the pressure level of 20 mm Hg. The FVC, FEV1/FVC and PEF values in this position were recorded and subjected for analysis. Paired t test was used, FVC (p= 0.551), FEV1/FVC (p=0.156), PEFR (p=0.339) values are statistically not significant. Abdominal Compression Binder has no effect on pulmonary function in Adult paraplegics.